Carbon nanotube dispersion and preparation method thereof
By using auxiliary dispersants of polyethylene glycol, polystyrene and cellulose-based components in the carbon nanotube dispersion, combined with the main dispersant, the problem of sharp increase in viscosity when the content of conductive materials increases is solved, and a carbon nanotube dispersion with high processability and storage stability is achieved.
Patent Information
- Application Number
- CN202480003970.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-19
- Filing Date
- 2024-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
The viscosity of the existing carbon nanotube dispersion increases dramatically when the content of conductive material increases, resulting in a decrease in processability and the viscosity changes significantly over time, affecting storage stability.
The auxiliary dispersant containing polyethylene glycol, polystyrene and cellulose-based components is used to combine the main dispersant to form a carbon nanotube dispersion, and the initial viscosity and viscosity stability of the dispersion are controlled through homogeneous mixing and dispersion treatment.
It is achieved to maintain appropriate initial viscosity and low viscosity change rate while maintaining carbon nanotube content at a predetermined level or higher level, improving the processability and storage stability of the dispersion.
Smart Images

Figure BDA0005307373940000101 
Figure BDA0005307373940000111
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0007983 filed on January 19, 2023, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present invention relates to a carbon nanotube dispersion and a method for preparing the same, wherein the carbon nanotube dispersion has excellent storage stability due to a small change in viscosity over time during storage at room temperature and high temperature, and is particularly suitable for use as a conductive material due to excellent conductivity. Background Art
[0005] Carbon nanotubes are macromolecules in which a hexagonal honeycomb graphite surface (one carbon atom is bonded to three other carbon atoms) is wound into a nanometer-sized diameter. Carbon nanotubes are hollow and therefore lightweight, and have electrical conductivity as good as that of copper, thermal conductivity as excellent as that of diamond, and tensile strength as good as that of steel. Depending on their winding shape, carbon nanotubes can be divided into single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), and rope-shaped carbon nanotubes.
[0006] Due to excellent conductivity, carbon nanotubes have recently been widely used as conductive materials for secondary batteries, but carbon-based conductive materials such as carbon nanotubes have the problem that the conductive materials cannot be evenly dispersed in the electrode slurry composition and are easily aggregated. If the conductive material aggregates in the electrode slurry composition, the conductive material cannot be evenly distributed in the active material layer during the process of forming the electrode, which also leads to performance degradation of the secondary battery. Therefore, various technologies are being studied to ensure that the conductive material is evenly dispersed in the electrode slurry composition.
[0007] Representatively, the attempt to increase dispersibility by introducing a dispersant together with the conductive material is the most common. Specifically, it is known to improve the method of dispersibility in a dispersed state by introducing a polymer component such as polyvinyl pyrrolidone (PVP) or hydrogenated nitrile butadiene rubber (HNBR) as a dispersant. However, when the above-mentioned components are used as dispersants, another problem is that when the content of the conductive material increases, the viscosity of the dispersion itself increases sharply, thereby reducing the processability of the dispersion itself, so when the above-mentioned components are used as a single dispersant, the content of the conductive material can not be significantly increased, thereby causing the improvement of conductivity to be limited. In addition, even when the above-mentioned components are used as a single dispersant to make the initial viscosity of the dispersion low, the viscosity of the dispersion also changes significantly over time, thereby causing the problem of the quality of the dispersion deteriorating during its distribution process.
[0008] Therefore, there is a need for development of a new carbon nanotube dispersion capable of maintaining the content of a conductive material at a predetermined level or higher while also maintaining the viscosity and viscosity stability at excellent levels.
[0009] Prior art literature
[0010] (Patent Document 1) KR 10-2125963B1 Summary of the invention
[0011] Technical issues
[0012] An object of the present invention is to provide a carbon nanotube dispersion capable of maintaining the carbon nanotube content in the dispersion at a predetermined level or higher while having a satisfactory initial viscosity of the dispersion itself and having excellent storage stability due to a low rate of change in viscosity over time.
[0013] Technical Solution
[0014] In order to achieve the above object, the present invention provides a carbon nanotube dispersion and a preparation method thereof.
[0015] Specifically, (1) the present invention provides a carbon nanotube dispersion comprising carbon nanotubes, a solvent, a primary dispersant and an auxiliary dispersant, wherein the auxiliary dispersant comprises polyethylene glycol, polystyrene and a cellulose-based component.
[0016] (2) In the above (1), the present invention provides a carbon nanotube dispersion, wherein the cellulose-based component is one or more selected from the group consisting of methyl cellulose, (hydroxypropyl) methyl cellulose, ethyl cellulose and hydroxypropyl cellulose.
[0017] (3) In the above (1) or (2), the present invention provides a carbon nanotube dispersion, wherein the polyethylene glycol is contained in an amount of 10 to 30 parts by weight based on a total of 100 parts by weight of the auxiliary dispersant.
[0018] (4) In any one of (1) to (3) above, the present invention provides a carbon nanotube dispersion, wherein the polystyrene is contained in an amount of 10 to 30 parts by weight based on a total of 100 parts by weight of the auxiliary dispersant.
[0019] (5) In any one of (1) to (4) above, the present invention provides a carbon nanotube dispersion, wherein the cellulose-based component is contained in an amount of 20 to 60 parts by weight based on a total of 100 parts by weight of the auxiliary dispersant.
[0020] (6) In any one of (1) to (5) above, the present invention provides a carbon nanotube dispersion, wherein the content of the auxiliary dispersant in the dispersion is 5 wt % to 100 wt % based on the content of the primary dispersant in the dispersion.
[0021] (7) In any one of (1) to (6) above, the present invention provides a carbon nanotube dispersion, wherein the primary dispersant is one or more selected from the group consisting of nitrile rubber (HNBR), styrene butadiene rubber, carboxymethyl cellulose, polyvinyl pyrrolidone and polyvinyl butyral.
[0022] (8) In any one of (1) to (7) above, the present invention provides a carbon nanotube dispersion, wherein the content of the primary dispersant in the dispersion is 0.1 wt% to 10.0 wt% based on the weight of the total dispersion.
[0023] (9) In any one of (1) to (8) above, the present invention provides a carbon nanotube dispersion, wherein the solvent is one or more selected from the following: N-methyl-2-pyrrolidone (NMP), methyl ethyl ketone (MEK), acetone and methyl butyl ketone (MBK).
[0024] (10) In any one of (1) to (9) above, the present invention provides a carbon nanotube dispersion, wherein the content of the carbon nanotubes in the dispersion is 3 wt% to 10 wt%.
[0025] (11) In any one of (1) to (10) above, the present invention provides a carbon nanotube dispersion wherein the viscosity change rate over one week is 3% or less.
[0026] (12) The present invention provides a method for preparing a carbon nanotube dispersion according to any one of (1) to (11), the method comprising: (S1) mixing carbon nanotubes, a solvent, a primary dispersant and an auxiliary dispersant, and (S2) dispersing the above mixture.
[0027] (13) In the above (12), the present invention provides a method for preparing a carbon nanotube dispersion, wherein the S1 step is performed in a homomixer for 0.5 hour to 2 hours.
[0028] (14) In the above (12) or (13), the present invention provides a method for preparing a carbon nanotube dispersion, wherein the S2 step is performed by a dispersion method selected from bead milling, ball milling and high-pressure homogenization.
[0029] Beneficial Effects
[0030] The carbon nanotube dispersion of the present invention has a content of carbon nanotubes in the dispersion at a predetermined level or higher, thus being able to achieve excellent conductivity, and also has an appropriate level of initial viscosity of the dispersion itself, thus having excellent processability.
[0031] Furthermore, the carbon nanotube dispersion has a low rate of change in viscosity over time during storage at high and low temperatures, and thus has excellent storage stability. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described in more detail.
[0033] It will be understood that the terms or words used in the specification and claims should not be interpreted as limited to having the meanings defined in commonly used dictionaries, but should be interpreted as having meanings and concepts consistent with the technical concept of the present invention based on the concept that the inventor can appropriately define the terms to best illustrate the principle of the present invention.
[0034] Carbon Nanotube Dispersion
[0035] The present invention provides a carbon nanotube dispersion comprising carbon nanotubes, a solvent, a primary dispersant and an auxiliary dispersant, wherein the auxiliary dispersant comprises polyethylene glycol, polystyrene and a cellulose-based component.
[0036] As mentioned above, when a polymer-based dispersant such as hydrogenated nitrile rubber (HNBR), which is known as a dispersant for typical carbon nanotube dispersions, is applied as a single dispersant, there is an effect of reducing the initial viscosity, but there is a problem that the viscosity increases significantly over time after the dispersion is prepared, and therefore, the inventors of the present invention have attempted to reduce the rate of change of viscosity over time by applying an auxiliary dispersant together with the polymer-based dispersant.
[0037] In particular, it has been determined that, in the present invention, the application of an auxiliary dispersant comprising at least three components of polyethylene glycol, polystyrene and a cellulose-based component together with the main dispersant makes it possible to reduce the rate of change in viscosity over time while suppressing an initial viscosity increase, and to maintain the carbon nanotube content of the dispersion at a predetermined level or higher.
[0038] Auxiliary dispersant
[0039] The auxiliary dispersant used in the present invention is characterized by comprising polyethylene glycol, polystyrene and a cellulose-based component.
[0040] 1) Polyethylene glycol
[0041] Polyethylene glycol is a polymer formed by dehydration condensation of a plurality of ethylene glycol molecules and has hydrophilic properties, so when applied to the carbon nanotube dispersion of the present invention, polyethylene glycol can be used to maintain a uniform phase with the solvent.
[0042] The weight average molecular weight (Mw) of the polyethylene glycol used in the present invention may be 100 g / mol to 5,000 g / mol, preferably 300 g / mol to 2,000 g / mol. If the weight average molecular weight of the polyethylene glycol is within the above range, it may have a technical advantage of being able to reduce the viscosity of the dispersion by suppressing the phase separation between the carbon nanotubes and the solvent.
[0043] The polyethylene glycol may be included in an amount of 10 to 30 parts by weight, preferably 15 to 25 parts by weight, based on 100 parts by weight of the auxiliary dispersant in total. If the content of the polyethylene glycol in the auxiliary dispersant is less than the above range, the effect achieved by the polyethylene glycol may be insufficient, and if the content of the polyethylene glycol is greater than the above range, the contents of other components are relatively reduced, so that the effect of improving the viscosity stability of the dispersion may not be fully achieved.
[0044] 2) Polystyrene
[0045] Polystyrene is a polymer formed by polymerization of a plurality of styrene single molecules, and when applied to the carbon nanotube dispersion of the present invention, polystyrene can be particularly used to reduce the viscosity of the dispersion.
[0046] The weight average molecular weight (Mw) of the polystyrene used in the present invention may be 800 to 50,000 g / mol, preferably 1,000 to 10,000 g / mol. If the weight average molecular weight of the polystyrene is within the above range, the effect of the polystyrene in reducing the viscosity of the dispersion may be particularly high.
[0047] The polystyrene may be included in an amount of 10 to 30 parts by weight, preferably 15 to 25 parts by weight, based on 100 parts by weight of the auxiliary dispersant in total. If the content of the polystyrene in the auxiliary dispersant is less than the above range, the effect achieved by the polystyrene may be insufficient, and if the content of the polystyrene is greater than the above range, the contents of other components are relatively reduced, so that the effect of improving the viscosity stability of the dispersion may not be fully achieved.
[0048] 3) Cellulose-based components
[0049] In the present invention, in addition to the above two components, a cellulose-based component is also used as an auxiliary dispersant. The cellulose-based component can be one or more selected from the following: methylcellulose, (hydroxypropyl) methylcellulose, ethyl cellulose and hydroxypropyl cellulose. The cellulose-based component significantly helps to suppress the increase in the viscosity of the dispersion over time and can improve the viscosity stability without losing the initial viscosity.
[0050] The cellulose-based component may be included in an amount of 40 to 80 parts by weight, preferably 50 to 70 parts by weight, based on a total of 100 parts by weight of the auxiliary dispersant. If the content of the cellulose-based component in the auxiliary dispersant is less than the above range, the effect achieved by the cellulose-based component may be insufficient, and if the content of the cellulose-based component is greater than the above range, the contents of other components are relatively reduced, so that the initial viscosity may be excessively increased.
[0051] The content of the auxiliary dispersant comprising the above three components in the dispersion may be 10 wt % to 100 wt %, preferably 20 wt % to 50 wt %, based on the content of the primary dispersant in the dispersion. If the content of the auxiliary dispersant is too low, the effect of the auxiliary dispersant in improving viscosity stability may not be significant, and if the content of the auxiliary dispersant is too high, the initial viscosity may become too high due to the presence of the auxiliary dispersant.
[0052] Primary dispersant
[0053] The above auxiliary dispersant is used to solve the problem of increased viscosity of the primary dispersant to be described below, and in the present invention, the following primary dispersant is used together with the above auxiliary dispersant to achieve sufficient dispersibility of the dispersion.
[0054] Specifically, the primary dispersant may be one or more selected from the group consisting of hydrogenated nitrile rubber (HNBR), styrene butadiene rubber, carboxymethyl cellulose, polyvinyl pyrrolidone, and polyvinyl butyral.
[0055] In the carbon nanotube dispersion of the present invention, the content of the primary dispersant in the dispersion may be 5 wt % to 100 wt %, preferably 10 wt % to 50 wt %, based on the content of the carbon nanotubes. In addition, the content of the primary dispersant may be 0.1 wt % to 10.0 wt %, preferably 0.5 wt % to 5 wt %, and particularly preferably 0.5 wt % to 3.0 wt %, based on the weight of the total dispersion. If the content of the primary dispersant is too low, the carbon nanotubes may not be sufficiently dispersed, and if the content of the primary dispersant is too high, the initial viscosity is excessively increased, making it impossible to increase the content of the carbon nanotubes in the dispersion to more than a predetermined level.
[0056] Solvents
[0057] The solvent is a medium for dispersing carbon nanotubes, and may be a water-based or oil-based solvent, and more specifically, may be one or more selected from the following: water, methanol, ethanol, propanol, acetone, dimethylformamide (DMF), dimethylacetamide, dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP).
[0058] Carbon Nanotubes
[0059] The carbon nanotubes serve as the conductive material in the dispersion of the present invention, and may be single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0060] The carbon nanotubes used in the present invention are not particularly limited, but may preferably have a carbon nanotube density of 20 kg / m 3 Up to 40kg / m 3 The bulk density can be 100m 2 / g to 400m 2 / g specific surface area. If the carbon nanotubes meet the above conditions, their electrical conductivity can be particularly excellent. At the same time, the bulk density can be calculated by filling a container with a specific volume with carbon nanotubes and then dividing the measured mass by the volume of the container. In addition, the specific surface area can be measured by the BET method, and more specifically, it can be calculated by using a specific surface area measuring device (BEL Japan Co., BELSORP-mini II) from the nitrogen adsorption at liquid nitrogen temperature (77K).
[0061] In the carbon nanotube dispersion of the present invention, the content of carbon nanotubes may be 3 wt % to 10 wt %, preferably 3 wt % to 6 wt %. The present invention is characterized in that a primary dispersant and an auxiliary dispersant are used together, thereby allowing the content of carbon nanotubes in the dispersant to be 3 wt % or more. Meanwhile, if the content of carbon nanotubes is too low, when the carbon nanotubes are used as a conductive material, etc., sufficient conductivity may not be achieved, and if the content of carbon nanotubes is too high, the viscosity of the dispersion is excessively increased, so that workability may be reduced.
[0062] In the carbon nanotube dispersion of the present invention, the viscosity change rate over one week may be 3% or less, preferably 2% or less. The viscosity change rate over one week is calculated by how much the viscosity increases during the course of one week when the dispersion is stored under the condition of 25°C for one week, and can be calculated by the following equation 1.
[0063] [Equation 1]
[0064] Viscosity change rate (%) = (viscosity after storage at 25°C for one week - viscosity at the time of dispersion preparation) / (viscosity at the time of dispersion preparation) * 100%
[0065] Meanwhile, the above viscosity can be measured by using a viscometer (TOKI Co., TV-25) and by starting measurement with a No. 1 rotor at 1 rpm and recording the value after 10 minutes.
[0066] The carbon nanotube dispersion of the present invention can reduce the viscosity change rate as described above by applying an auxiliary dispersant, and can achieve excellent viscosity stability. Meanwhile, if the auxiliary dispersant is not applied, the viscosity change rate may be as high as 10% or more.
[0067] Method for preparing carbon nanotube dispersion
[0068] The present invention provides a method for preparing the above-mentioned carbon nanotube dispersion, and specifically provides a method for preparing the carbon nanotube dispersion, the method comprising (S1) mixing carbon nanotubes, a solvent, a primary dispersant and an auxiliary dispersant, and (S2) dispersing the above-mentioned mixture.
[0069] In the method for preparing a carbon nanotube dispersion of the present invention, the carbon nanotubes, the solvent, the primary dispersant and the auxiliary dispersant are the same as described above.
[0070] Meanwhile, the step S1 of mixing all the above components can be performed in a homogenizing mixer for 0.5 to 2 hours, preferably 0.5 to 1.5 hours. If a homogenizing mixer is used during the mixing process, the components can be mixed more uniformly, and in particular, if the mixing is performed for the above period of time, a mixture can be formed without deteriorating the quality of the carbon nanotubes.
[0071] In addition, in step S2, the formed mixture can be dispersed to prepare a final dispersion. In the dispersion step, the physical properties of the carbon nanotubes in the dispersion can become uniform. At the same time, the method for dispersion can be selected from bead milling, ball milling and high pressure homogenization, and preferably, it can be bead milling. If the above-mentioned dispersion method is used, a more uniform dispersion can be achieved, so that the viscosity of the obtained carbon nanotube dispersion can be kept low.
[0072] The carbon nanotube dispersion prepared by the preparation method of the present invention may have an initial viscosity of 15,000 cps or less, preferably 14,000 cps or less.
[0073] Hereinafter, the present invention will be described in more detail with reference to embodiments and experimental embodiments. However, the present invention is not limited by these embodiments and experimental embodiments. Embodiments according to the present invention can be modified into other various forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided to more fully describe the present invention to those skilled in the art.
[0074] Material
[0075] Prepared with 36kg / m 3 The bulk density and 186m 2 / g of carbon nanotubes with a specific surface area of 1.17 W / cm. In addition, hydrogenated nitrile rubber (HNBR) was prepared as a main dispersant, and N-methyl-2-pyrrolidone (NMP) was prepared as a solvent.
[0076] As auxiliary dispersants of the embodiments, auxiliary dispersant A in which polyethylene glycol (weight average molecular weight: 750 g / mol), polystyrene (weight average molecular weight: 2,500 g / mol) and methyl cellulose are mixed in a weight ratio of 1:1:3, and auxiliary dispersant B in which polyethylene glycol (weight average molecular weight: 750 g / mol), polystyrene (weight average molecular weight: 2,500 g / mol) and (hydroxypropyl) methyl cellulose are mixed in a weight ratio of 1:1:3 are used.
[0077] As auxiliary dispersants of comparative examples, auxiliary dispersant C which does not contain a cellulose-based component and in which polyethylene glycol (weight average molecular weight: 750 g / mol), polystyrene (weight average molecular weight: 2,500 g / mol) and ethylene glycol are mixed in a weight ratio of 1:1:1, auxiliary dispersant D in which polystyrene (weight average molecular weight: 2,500 g / mol) and ethylene glycol are mixed in a weight ratio of 1:1, auxiliary dispersant E in which polyethylene glycol and methylcellulose are mixed in a weight ratio of 1:3, and auxiliary dispersant F in which polystyrene and methylcellulose are mixed in a weight ratio of 1:3 were used.
[0078] Meanwhile, the auxiliary dispersant was prepared by pre-dissolving the components used in each auxiliary dispersant in an NMP solvent and then mixing them in a slurry mixer at 1300 rpm for 10 minutes.
[0079] Examples and Comparative Examples
[0080] The carbon nanotubes, solvent, primary dispersant and auxiliary dispersant of the above materials were mixed in a homogenizing mixer for 1 hour. Afterwards, dispersion was prepared by grinding at 3000 rpm for 30 minutes using a bead mill. The concentration of the carbon nanotubes used in each of the embodiments and comparative examples and the type and content (based on the gross weight of the dispersion) of the primary dispersant and auxiliary dispersant used are summarized in Table 1 below.
[0081] [Table 1]
[0082]
[0083] Experimental Example 1. Determination of viscosity stability of dispersions during storage at room temperature
[0084] The initial viscosity of the carbon nanotube dispersion prepared in each of Examples and Comparative Examples was measured, and the viscosity thereof was measured again after being stored at 25° C. for one week. The viscosity change rate was calculated from the measured viscosity and is summarized in Table 2 below.
[0085] [Table 2]
[0086]
[0087] As can be determined in Table 2 above, when Examples 1 and 3 applying the same primary dispersant and carbon nanotube content are compared with Comparative Examples 1, 3, and 4, it can be seen that Examples 1 and 3 applying the auxiliary dispersant component of the present invention at the same time show a lower viscosity change rate. In particular, Comparative Example 1 applying the auxiliary dispersant C not containing a cellulose-based component shows a slightly lower value than the examples of the present invention in terms of initial viscosity, but in terms of viscosity stability, has a viscosity change rate of 16% or more, thereby indicating that the viscosity stability during room temperature storage is greatly reduced. In addition, Comparative Example 3, in which the auxiliary dispersant D not containing a cellulose-based component or polyethylene glycol is used as an auxiliary dispersant, has a low initial viscosity, and the viscosity change rate itself is lower than that of the other comparative examples, but when the appearance of the dispersion is observed after one week of storage, although the other examples and comparative examples all show good results, Comparative Example 3 shows phase separation from the solvent. That is, the structure in which the carbon nanotubes are dispersed in the dispersion collapses, which means that the dispersion of Comparative Example 3 loses its function as a dispersion even if it is stored at room temperature for only a short time after preparation. Comparative Example 4 in which no auxiliary dispersant was applied also had a high viscosity change rate and was therefore determined to have reduced viscosity stability. In addition, Comparative Examples 5 and 6 in which only part of the auxiliary dispersant component of the present invention was used had problems such as too high initial viscosity (Comparative Example 5) or separation from the solvent phase (Comparative Example 6) despite low initial viscosity and low viscosity change rate.
[0088] In addition, contents similar to those in the above description were determined from the results of comparing Example 2 in which a primary dispersant having a high molecular weight was applied and Comparative Example 2. Comparative Example 2 showed a significantly higher viscosity change rate than Example 2, thereby determining that regardless of the type of the primary dispersant and the content of the carbon nanotubes, the viscosity stability may vary depending on the component of the applied auxiliary dispersant.
[0089] Experimental Example 2. Determination of viscosity stability of dispersions during high temperature storage
[0090] For each of the dispersions of Example 1 and Comparative Example 1, the viscosity stability during high temperature storage was additionally determined. When the dispersion was stored under the condition of 60° C., the viscosity thereof was measured after storage for 3 days instead of 7 days in consideration of the fact that the viscosity increases more sharply under high temperature conditions. The measured initial viscosity, the viscosity after storage for 3 days, and the viscosity change rate were calculated and shown in Table 3 below.
[0091] [Table 3]
[0092] Example 1 Comparative Example 1 Initial viscosity (cps) 13500 9500 Viscosity after 3 days storage (cps) 17000 13000 Viscosity change rate (%) 25.9% 36.8%
[0093] As can be determined from the results of Table 3 above, both Example 1 and Comparative Example 1 have a drastic increase in viscosity when stored at high temperatures, but it is determined that the viscosity change rate of Comparative Example 1 is higher.
[0094] From the results, it was confirmed that the auxiliary dispersant of the present invention has the effect of suppressing viscosity change not only during storage at room temperature but also during storage at high temperature.
Claims
1. A carbon nanotube dispersion comprising: Carbon nanotubes; Solvents; primary dispersant; and Auxiliary dispersants, wherein the auxiliary dispersants comprise polyethylene glycol, polystyrene and a cellulose-based component. 2 . The carbon nanotube dispersion according to claim 1 , wherein the cellulose-based component is one or more selected from the group consisting of methyl cellulose, (hydroxypropyl) methyl cellulose, ethyl cellulose and hydroxypropyl cellulose. 3 . The carbon nanotube dispersion according to claim 1 , wherein the polyethylene glycol is included in an amount of 10 to 30 parts by weight based on a total of 100 parts by weight of the auxiliary dispersant. 4 . The carbon nanotube dispersion according to claim 1 , wherein the polystyrene is included in an amount of 10 parts by weight to 30 parts by weight based on 100 parts by weight in total of the auxiliary dispersant. 5 . The carbon nanotube dispersion according to claim 1 , wherein the cellulose-based component is included in an amount of 40 to 80 parts by weight based on a total of 100 parts by weight of the auxiliary dispersant. 6 . The carbon nanotube dispersion according to claim 1 , wherein the content of the auxiliary dispersant in the dispersion is 5 wt % to 100 wt % based on the content of the primary dispersant in the dispersion. 7 . The carbon nanotube dispersion according to claim 1 , wherein the primary dispersant is one or more selected from the group consisting of nitrile butadiene rubber (HNBR), styrene butadiene rubber, carboxymethyl cellulose, polyvinyl pyrrolidone, and polyvinyl butyral. 8 . The carbon nanotube dispersion according to claim 1 , wherein the content of the primary dispersant in the dispersion is 0.1 wt % to 10.0 wt % based on the weight of the total dispersion. 9 . The carbon nanotube dispersion according to claim 1 , wherein the solvent is one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), methyl ethyl ketone (MEK), acetone, and methyl butyl ketone (MBK). 10 . The carbon nanotube dispersion according to claim 1 , wherein the content of the carbon nanotubes in the dispersion is 3 wt % to 10 wt %.
11. The carbon nanotube dispersion according to claim 1, wherein a viscosity change rate over one week is 3% or less.
12. A method for preparing the carbon nanotube dispersion according to claim 1, the method comprising: (S1) mixing carbon nanotubes, a solvent, a primary dispersant and an auxiliary dispersant; as well as (S2) dispersing the above mixture. 13 . The method according to claim 12 , wherein the step S1 is performed in a homogenizing mixer for 0.5 to 2 hours.
14. The method according to claim 12, wherein the S2 step is performed by a dispersion method selected from the group consisting of bead milling, ball milling and high-pressure homogenization.
Citation Information
Patent Citations
Access control system and access control method using the same
KR1020230007983A
Carbonnanotube dispersion and method of preparing the same
KR102125963B1